Exploiting molecular symmetry reduction to enrich liquid crystal phase diversity. Issue 10 (9th August 2019) - Ester, David F.; Williams, Vance E.
ABSTRACT: The strategic tuning of liquid crystalline phase behaviour by adjusting molecular symmetry was investigated. A family of sixteen symmetrical and unsymmetrical 2, 6-di(4ʹ-n-alkoxybenzoyloxy) naphthalene derivatives were prepared and their liquid crystal properties examined by differential scanning calorimetry, polarised optical microscopy, and x-ray diffraction. All mesogens formed nematic phases, with longer-chain analogues also exhibiting smectic C phases at lower temperatures. Melting temperatures of the compounds strongly depend on molecular symmetry, whereas clearing transitions are relatively insensitive to this effect. A detailed analysis indicates that the clearing point can be predicted based on the nature of the terminal alkyl chains, with only a secondary effect from molecular symmetry. Moreover, low symmetry molecules showed a greater tendency to form smectic C phases, which was ascribed to the selective depression of the melting point versus the SmC-N transition. This demonstrates that molecular symmetry-breaking is a valuable tool both for tuning liquid crystalline phase range and for increasing a material's polymorphism. Graphical Abstract: